ADO.NET 3.5 cookbook - Hamilton, Bill, 1964- (O'Reilly, 2008)
"Now updated for Visual Studio 2008, .NET Framework 3.5, and SQL Server 2008, ADO.NET 3.5 Cookbook demonstrates how you can work with LINQ and other new .NET technologies to make data access easier and more efficient." "Complete C♯ code samples are presented together with output, so you can use this book without loading the actual code; in addition, Visual Basic code is available on the book's web site. Best of all, every recipe offers explanations of how and why each solution works - as well as its requirements, trade-offs, and drawbacks - so you will learn to adapt this book's problem-solving techniques to different situations."--Jacket